2017
DOI: 10.1111/1753-0407.12618
|View full text |Cite
|
Sign up to set email alerts
|

Performance of non‐traditional hyperglycemia biomarkers by chronic kidney disease status in older adults with diabetes: Results from the Atherosclerosis Risk in Communities Study

Abstract: In older adults with severe or very severe CKD, HbA1c, glycated albumin, and fructosamine were not highly correlated with fasting glucose. The results suggest there may be no particular advantage of glycated albumin or fructosamine over HbA1c for monitoring glycemic control in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…Kidney disease assessed by low eGFR was strongly related to discordant HbA1c and fasting glucose values. It is well established that in chronic kidney disease HbA1c may yield biased results for glycemic control . As an example, a low correlation was recently found between HbA1c and fasting glucose ( r = 0.52) in people with diabetes and severe chronic kidney disease …”
Section: Discussionmentioning
confidence: 99%
“…Kidney disease assessed by low eGFR was strongly related to discordant HbA1c and fasting glucose values. It is well established that in chronic kidney disease HbA1c may yield biased results for glycemic control . As an example, a low correlation was recently found between HbA1c and fasting glucose ( r = 0.52) in people with diabetes and severe chronic kidney disease …”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that the dataset may be limited, Jung et al nevertheless give an intriguingly negative answer to the first question, of the reliability of HbA1c with kidney disease. Using Deming regression analysis, Jung et al showed that the correlation between HbA1c and fasting glucose weakens as renal function worsens, and, moreover, that this appears particularly to be the case in people with anemia (hemoglobin <130 and <120 g/L for men and women, respectively), confirming earlier observations .…”
Section: How Does Chronic Kidney Disease Affect Hba1c?mentioning
confidence: 99%
“…How, then, should we assess a given diabetic person's degree of glycemic control in the presence of CKD (or of anemia, which, per Jung et al, was, even without CKD, also associated with a reduction in the correlation between HbA1c and fasting glucose)? Jung et al suggest the use of continuous glucose monitoring to estimate average glucose. Although becoming recognized as an important tool, this technology is not as generally available as the simpler self‐monitoring of blood glucose (SMBG).…”
Section: How Does Chronic Kidney Disease Affect Hba1c?mentioning
confidence: 99%
See 2 more Smart Citations